(untitled) (Journal of Enam Medical College, 2013)
Biotechnology is the knowledge and techniques of developing and using biological systems for deriving special products and services. The age-old technology took a new turn with the advent of recombinant DNA techniques, and boosted by the development of other molecular biological techniques, cell culture techniques and bioinformatics. Medical biotechnology is the major thrust area of biotechnology. It has brought revolutions in medicine quick methods for diagnosing diseases, generation of new drugs and vaccines, completely novel approach of treatment are only a few to mention. The industrial and financial bulk of the industry mushroomed very rapidly in the last three decades, led by the USA and western advanced nations. Asian countries like China, India, South Korea, Taiwan and Singapore joined late, but advancing forward in a big way. In all the Asian countries governments supported the initiatives of the expert and entrepreneur community, and invested heavily in its development. Bangladesh has got great potential in developing biotechnology and reaping its fruits. However, lack of commitment and patriotism, and too much corruption and irresponsibility in political and bureaucratic establishment are the major hindrance to the development of biotechnology in Bangladesh. DOI: http://dx.doi.org/10.3329/jemc.v3i1.13873 J Enam Med Col 2013; 3(1): 32-46